Environmental and energy law : international dimensions - Viñuales, Jorge E., 1973-; Lees, Emma; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2017)
This Research Review covers the main topics and dimensions of environmental and energy law in its contemporary expression. It discusses foundational material for those interested in understanding the development of the field and conducting research on the myriad of questions raised by transitions to sustainability. Particular emphasis is placed on the systematisation of the material. The Research Review discusses articles that cover international dimensions, including principles, substantive areas of regulation and implementation techniques as well as the European dimensions broadly understood, including EU law and other regional approaches (the UNECE) and distinguishing sector-specific and transversal regulation. It also looks at the transnational, comparative and domestic dimensions and major questions arising from selected English-speaking jurisdictions. Edited by two recognised experts in the field, this research review will provide a solid foundation for the study of environmental and energy law.
15. Richard Macrory (2008), 'New Approaches to Regulatory Sanctions', Environmental Law and Management, 20, 210-14 -- 16. Colin T. Reid (2011), 'The Privatisation of Biodiversity? Possible New Approaches to Nature Conservation Law in the UK', Journal of Environmental Law, 23 (2), July, 203-31 -- 17. Richard Lazarus (2012), 'The National Environmental Policy Act in the U.S. Supreme Court: A Reappraisal and A Peek Behind the Curtains', Georgetown Law Journal, 100, 1507-86 -- 18. Gerd Winter (2013), 'The Rise and Fall of Nuclear Energy Use in Germany: Processes, Explanations and the Role of Law', Journal of Environmental Law, 25 (1), March, 95-124 -- 19. Alex L. Wang (2013), 'The Search for Sustainable Legitimacy: Environmental Law and Bureaucracy in China', Harvard Environmental Law Review, 37, 365-440 -- 20. Richard B. Stewart (1992), 'Environmental Regulation and International Competitiveness', Yale Law Journal, 102 (8), 2039-106 -- 21. Peter Cane (2001), 'Are Environmental Harms Special?', Journal of Environmental Law, 13 (1), 3-20 -- 22. Jody Freeman and Daniel A. Farber (2005), 'Modular Environmental Regulation', Duke Law Journal, 54 (4), February, 795-902 -- 23. Elizabeth Fisher, Bettina Lange, Eloise Scotford and Cinnamon Carlarne (2009), 'Maturity and Methodology: Starting a Debate about Environmental Law Scholarship', Journal of Environmental Law, 21 (2), 213-50 -- 24. Ole W. Pederson (2013), 'Modest Pragmatic Lessons for a Diverse and Incoherent Environmental Law', Oxford Journal of Legal Studies, 33 (1), Spring, 103-31
The recommended readings are available in the print version, or may be available via the link to your library's holdings
Keywords: právo životního prostředí; mezinárodní právo životního prostředí; energetika; environmental law; international environmental law; energy industries; e-knihy online; e-books online